2015
DOI: 10.1007/s11104-015-2542-1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological interpretations of nitrogen isotope ratios of terrestrial plants and soils

Abstract: Background Knowledge of biological and climatic controls in terrestrial nitrogen (N) cycling within and across ecosystems is central to understanding global patterns of key ecosystem processes. The ratios of 15 N: 14 N in plants and soils have been used as indirect indices of N cycling parameters, yet our understanding of controls over N isotope ratios in plants and soils is still developing. Scope In this review, we provide background on the main processes that affect plant and soil N isotope ratios. In a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

34
405
6
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(479 citation statements)
references
References 210 publications
34
405
6
6
Order By: Relevance
“…Therefore, most biologically active N forms remain in the layer, mainly within cells. Below this peak, both N content and δ N decrease with depth, as reported by Craine et al (2015). The relatively lower values of the upper layers are the results of (i) high C/N ratios of the aboveground plant residuals; (ii) low SOM content, due to intensive cultivation; and (iii) low microbiological activity.…”
Section: Figsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, most biologically active N forms remain in the layer, mainly within cells. Below this peak, both N content and δ N decrease with depth, as reported by Craine et al (2015). The relatively lower values of the upper layers are the results of (i) high C/N ratios of the aboveground plant residuals; (ii) low SOM content, due to intensive cultivation; and (iii) low microbiological activity.…”
Section: Figsupporting
confidence: 67%
“…However, generally on a global scale, values in soil vary between -5 and + 12.6‰ (Craine et al 2015). At the landscape scale, in the morphologically deeper positions where temporary water saturation can occur, the proportion of N is generally higher due to increased denitrification activity (Mukundan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In general, nitrogen in plants comes from soil nitrogen pool (Vallano and Sparks, 2013 (Austin and Vitousek, 1998;Craine et al, 2015). The results in this study show that δ…”
mentioning
confidence: 68%
“…In addition, the results of a past study suggested that δ 15N values of plants and soils became low caused by high rainfall and low temperature at high altitude localities (Mariotti et al, 1980). However, Craine et al (2015) found that δ 15 N became enriched with dropping MAP and ascending MAT as MAT is over -0.5°C. However, the values were stable for MAT lower than -0.5°C.…”
mentioning
confidence: 96%
“…Nitrogen is a nutrient that regulates primary production in most ecosystems (Arbestain et al 2008) and its cycle affects almost all aspects of the functioning of an ecosystem (Vitousek et al 1997;Craine et al 2015). The nitrogen cycle in the ecosystem is complex with several transformations, feedback and interactions with other important biogeochemical elements (LeBauer, Treseder 2008;Thomas et al 2013).…”
mentioning
confidence: 99%